Protective Effect of Aqueous Extract of Lawsonia Inermis (Henna) Leaves on Acetylsalicylic Acid Induced Gastric Mucosal Toxicity in Adult Albino Rats (Journal of Fatima Jinnah Medical University, 2024)
Background: Non-steroidal anti-inflammatory drugs are the over-the-counter available medicine and is a major cause of the peptic ulcer disease. Large number of pharmaceuticals drugs are used to treat this but have many side effects. L.inermis is a plant derived drug and have gastroprotective effect.Subject and Methods: 36 Healthy albino rats of either sex were purchased and kept in controlled environment. These are mainly divided into three groups named as Group A, Group B and Group C having 12 rats in each group. Leaves were dried in shade and kept in oven at 40ºC for a week. The aqueous extract was prepared by mixing 25 gm of henna powder with 250 ml of distilled water for 12 hours then cooled and filtered by Buchner funnel and filter paper. The solvent will then be dried and concentrated using Rotary evaporator at 50°C. Extract was used in dose of 200mg/kg and aspirin was used in the dose of 100mg / kg drug solution is prepared. Six animals were sacrificed from each group on day 8th and 15th. Macroscopic ulcer was identified and ulcer index was calculated by using method described by Ganguly. Fibroblast, inflammatory cells, congested blood vessels were counted by micrometry. SPSS version 21 was used to statistically analyse the dataResults: Aspirin alone group have more ulcer, congested blood vessels, and increased number of fibroblasts compared to control and L.inermis group. Conclusion: This confirms that L. inermis not only counteract the harmful effects caused by the aspirin on gastric mucosa but also helps in repairing and healing process at the site of injury brought by the aspirin. Histological studies of injured site, when compared with the control, shows a organized pattern of collagen, fibroblast and inflammatory cells.
Keywords: L inermis; ulcer index; fibroblasts; peptic ulcer